2009
DOI: 10.1590/s0256-01002009000100007
|View full text |Cite
|
Sign up to set email alerts
|

The extent and practice of inclusion in independent schools in South Africa

Abstract: In line with international trends in education, South Africa has embraced inclusive education as the means by which learners who experience barriers to learning will be educated. As inclusion is beginning to be realised in South African schools, a gap in the em erging research base on inclusive education is that of inclusion in the independent sector. A study was undertaken to establish the extent to which learners who experience barriers to learning are included in independent schools belonging to ISASA (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
0
18
0
6
Order By: Relevance
“…In South Africa the development of barriers to learning were associated mostly with the intrinsic factors (internal) that is medical and disability models (Waltons 2006;Engelbrecht et al 2008). However there has been a paradigm shift in the way barriers to learning were conceptualized in South Africa, a shift from the understanding that specialized needs stem from the learner which often resulted in the identification and labeling of learners thus separating them from their peers (Pather 2007).…”
Section: Conceptualization Of Barriers To Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Africa the development of barriers to learning were associated mostly with the intrinsic factors (internal) that is medical and disability models (Waltons 2006;Engelbrecht et al 2008). However there has been a paradigm shift in the way barriers to learning were conceptualized in South Africa, a shift from the understanding that specialized needs stem from the learner which often resulted in the identification and labeling of learners thus separating them from their peers (Pather 2007).…”
Section: Conceptualization Of Barriers To Learningmentioning
confidence: 99%
“…For example in their work Walton et al (2009) found in independent schools that inclusive teaching strategies that were applied often were cooperative learning, peer tutoring, modification of the assessments tasks to suit the needs of the learners, marking and spelling concessions and providing extra-time for learners with learning barriers. This could maybe be cited for the high academic results in independent schools though the same cannot be said about the public schools.…”
Section: Inclusive Pedagogical Practices In the South African Classromentioning
confidence: 99%
“…' Mathibe (2007) observes that teachers' professional development needs to focus on giving them appropriate attitudes, knowledge, skills and values to perform their tasks well and resourcefully. This is even more critical in inclusive education where teachers need to know and understand what barriers to learning are, how to address them, as well as get hands-on training in classroom strategies that promote inclusion (Walton et al, 2009). This cannot be achieved using one-off training sessions as these have already been shown to be ineffective (Lessing and de Wit, 2007).…”
Section: What Is the Significance Of Professional Development In Inclmentioning
confidence: 99%
“…We are developing teachers to work in contexts that are ideal and do not exist for the majority -perhaps this is one reason why so many of our teachers become disillusioned and lose interest in teaching (Olivier & Wood 2007;Pretorius & De Villiers 2009). driven learning when they are faced with large classes, time constraints and many other barriers to effective learning that exist in our educational institutions (Walton, Nel, Hugo & Muller 2009). Drawing from my experience with HIV education, a critical pedagogical approach assumes that teachers have engaged both in critical selfreflection, and how they could engage learners to do the same.…”
Section: Relevance Of Curriculum To the Current Social Realitymentioning
confidence: 99%